Synthesis of Binuclear Complex Compound of [Fe(L)(NCS)Â¬2]2oks (L = 1,10-phenantrolin and 2,2â€™-bypiridine) - Male, Yusthinus T; Tehubijuluw, Helna; Pelata, Paulina M. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2013)
The paramagnetic complex [Fe(fen)(NCS)2]2oks have been synthesized in methanol solution using 1-10 phenantrolin, 2,2 '-bipyridine, NCS- ligands and oxalate as bridging ligand. Synthesis of Fe (II) with ligands phenantrolin produced three complexes is paramagnetic compounds each with a value of magnetic moment (Î¼) of 5.98 BM, 7.34 BM and 6.00 BM, respectively. For complexes with bipyridine ligand complexes obtained two diamagnetic compounds with the magnetic moment (Î¼) was 3.57 BM and 3.50 BM, respectively. It could concluded that the field strength of bipyridine ligand cannot be reduced by NCS- ligand. Analysis results showing that the synthesized compound is a binuclear complex with [Fe(fen)(NCS)2]2oks molecular formula. This conclusion was supported by the measurement of conductivity, magnetic moment, IR spectroscopy and XRD analysis.